A bacterial acyl aminoacyl peptidase couples flexibility and stability as a result of cold adaptation. (7th November 2016) - Brocca, Stefania; Ferrari, Cristian; Barbiroli, Alberto; Pesce, Alessandra; Lotti, Marina; Nardini, Marco
Abstract : Life in cold environments requires an overall increase in the flexibility of macromolecular and supramolecular structures to allow biological processes to take place at low temperature. Conformational flexibility supports high catalytic rates of enzymes in the cold but in several cases is also a cause of instability. The three‐dimensional structure of the psychrophilic acyl aminoacyl peptidase from Sporosarcina psychrophila ( Sp AAP) reported in this paper highlights adaptive molecular changes resulting in a fine‐tuned trade‐off between flexibility and stability. In its functional form Sp AAP is a dimer, and an increase in flexibility is achieved through loosening of intersubunit hydrophobic interactions. The release of subunits from the quaternary structure is hindered by an 'arm exchange' mechanism, in which a tiny structural element at the N terminus of one subunit inserts into the other subunit. Mutants lacking the 'arm' are monomeric, inactive and highly prone to aggregation. Another feature of Sp AAP cold adaptation is the enlargement of the tunnel connecting the exterior of the protein with the active site. Such a wide channel might compensate for the reduced molecular motions occurring in the cold and allow easy and direct access of substrates to the catalytic site, rendering transient movements between domains unnecessary. Thus, cold‐adapted Sp AAP has developed a molecular strategy unique within this group of proteins: it is able to enhance the flexibility of each functional unit while still preserving sufficient stability. Database: Structural data are available in the Protein Data Bank under the accession number5L8S . Abstract : Here we describe structural strategies of cold adaptation in a bacterial acyl‐aminoacyl peptidase. Among them, an arm‐exchange dimerization mechanism represents an elegant structural and functional solution to enhance the flexibility yet preserving stability. Cold adaptation is also achieved by the widening of a channel which allows direct access of substrates to the catalytic site, without the need of transient movements.